Validation of Acute Gastroenteritis-related International Classification of Diseases, Clinical Modification Codes in Pediatric and Adult US Populations. (18th October 2019) - Pindyck, Talia; Hall, Aron J; Tate, Jacqueline E; Cardemil, Cristina V; Kambhampati, Anita K; Wikswo, Mary E; Payne, Daniel C; Grytdal, Scott; Boom, Julie A; Englund, Janet A; Klein, Eileen J; Halasa, Natasha; et al.
Abstract: International Classification of Diseases diagnostic codes are used to estimate acute gastroenteritis (AGE) disease burden. We validated AGE-related codes in pediatric and adult populations using 2 multiregional active surveillance platforms. The sensitivity of AGE codes was similar (54% and 58%) in both populations and increased with addition of vomiting-specific codes.